Photographs of Old Watkins Family Photographs - Watkins, Howard::::::::: (1988)
Rose (Watkins) Katzenellenbogen, Taube (Ager) (Weiner) Katzenellenbogen, Irving Fine, Beatrice (Batsheva Eitan) Katzenellenbogen, Esther (Weiner) Fine, and Leah Sokolovsky (8x10) 1936 Family photograph just before leaving New York City for San Francisco